A new model with delay for mosquito population dynamics - Hui Wan; Huaiping Zhu (Mathematical Biosciences and Engineering, 2014)
In this paper, we formulate a new model with maturation delay formosquito population incorporating the impact of blood meal resourcefor mosquito reproduction. Our results suggest that except for theusual crowded effect for adult mosquitoes, the impact of blood mealresource in a given region determines the mosquito abundance, it isalso important for the population dynamics of mosquito which mayinduce Hopf bifurcation. The existence of a stable periodic solutionis proved both analytically and numerically. The new model formosquito also suggests that the resources for mosquito reproductionshould not be ignored or mixed with the impact of blood mealresources for mosquito survival and both impacts should beconsidered in the model of mosquito population. The impact ofmaturation delay is also analyzed.